PHYLOGENETIC ANALYSIS OF INTERFERON-ALPHA IN CATTLE - N. Tursunbay; E. Shevtsova; A. Ryskeldina; K. Mukanov; A. Nametov; A. Shevtsov; A. Kairzhanova (Animal Health and Biosafety, 2026)
Interferons-α (IFN-α) in cattle belong to the multigene family of type I interferons, whose evolution is associated with duplications, deletions, pseudogenization, and nomenclatural ambiguity regarding subtypes in Bovidae. The aim of the study was to obtain and phylogenetically characterize IFN-α gene fragments in Kalmyk cattle relative to reference sequences of Bovidae. Genomic DNA was isolated from hair follicles of three animals. IFN-α fragments were amplified using a two-step nested PCR method, cloned into the pGEM-T Easy vector, and recombinant clones were selected using colony PCR. After Sanger sequencing and manual verification of contigs, 68 high-quality sequences were included in the phylogenetic analysis. The reference dataset, generated based on a BLAST search for Bovidae IFN-α sequences in NCBI, included 143 unique sequences after removal of redundant entries. Phylogenetic reconstruction was performed using the maximum likelihood method based on amino acid alignment with the JTT+G model in MEGA12. Nested PCR yielded a specific amplicon of approximately 550 bp; colony PCR identified 74 clones out of 96 with an insert of the expected size, of which 68 were used for the final analysis. The sequences under study were distributed across six major clusters associated with Bo-alpha-A, Bo-alpha-B, alpha-C, alpha-F, alpha-G, and the mixed alpha-1/H-like/B-like cluster, as well as across two transitional zones with reduced bootstrap support. The most represented cluster was alpha-G—26 out of 68 clones (38.2%). Mixed clustering with sequences from Bos taurus, Bos indicus, Bos javanicus, Bison bison, Bos mutus, and Bubalus spp. confirms that the IFN-α structure in Bovidae does not follow a simple species-specific model but reflects the complex evolution of a multigene family. The identified ambiguity of clusters with different historical and automatic NCBI annotations underscores the need for cautious interpretation of IFN-α subtype affiliation. The data obtained form an initial library of IFN-α sequences from Kalmyk cattle and provide a basis for further analysis of the full IFNA locus, individual genotyping, and functional evaluation of recombinant IFN-α variants.